Pengaruh Penambahan Molases sebagai Sumber Glukosa terhadap Karakteristik Fisiko-Kimia Silase Rumput Gajah: The Effect of Molasses Addition as a Glucose Source on the Physic-chemical Characteristics of Elephant Grass Silage (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
This study aimed to examine the molasses addition as a glucose source in the process of elephant grass silage. A completely randomized design consisting of five treatments and five replications was used in this study. The treatments were P1: elephant grass (EG) as control, P2: EG + 2.5% molasses, P3: EG + 5% molasses, P4: EG + 7.5% molasses and P5: EG + 10% molasses based on dry matter. All the treatments were ensiled for 30 days. The parameters included physical quality were aroma, mold growth, texture while the chemical quality parameters were pH, dry matter, dry matter loss, and fleigh value. The data were analyzed for variance and if there were differences between treatments, the Duncan's test was conducted at the 5% level. The results showed that 10% molasses addition had a significant effect (p